Online Food Ordering System - Wong, Chun Chuan; Chuah, Chai Wen (Applied Information Technology And Computer Science, 2021)
The online food ordering system is a web-based system that is developed for restaurant Shu Xiang Lou and its customers. The restaurant is a hot pot restaurant and they run their business physically in Kuala Lumpur. An interview is conducted with the restaurant’s manager and had found that most of their customer needs to wait for a long time to collect the takeaway order. There is also the potential to lose customers when the phone line is engaged. Besides that, a fake order is an issue that may lead to the restaurant's financial risk as there are real cases that happened in the real world. Another problem found from the interview is that there is difficulty in providing appropriate and updated food information. Also, the manual calculation of the sales report in the restaurant is better to replace by the system and do it automatically. Hence, this project plan to develop a web-based system to handle the order process. The method uses to develop the system is object-oriented system development (OOSD). Java is the main programming language use to develop the system. The system is developed by using Model-View-Control (MVC) framework. A payment gateway is used in the system to prevent the fake order issue. The system also allows updating the restaurant menu easily. A sales report is also calculating automatically by the system. There is strong password management and encryption method to ensure system confidentiality.